Implementasi Media Promosi Katalog Baju yang Lebih Interaktif Menggunakan Aplikasi Augmented Reality - Sutianto, Nanang; Wulandari, Sri (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The current technological advancement are progressing rapidly in line with the changing times. With the current pace of development, many people, especially teenagers, are keen on following fashion trends. This has led to increased competition in the fashion catalog industry. Many industries require information technology innovation, including the products offered to attract customers' attention. Typically, catalog industries advertise their products using posters, photos, or videos. However, these methods are less interactive and engaging as promotional media ideas in the current digital era. One technology that can address this issue is Augmented Reality (AR), which combines virtual objects with the real-world environment captured by the camera, making virtual objects appear integrated into the real world. By using Mobile Augmented Reality (AR) applications and with the help of our smartphones, we can view virtual clothing catalog objects on our smartphones, making them appear as if they were real. Moreover, users can virtually try on clothing over their own images, providing them with a better understanding of how the clothing will look when worn. This can create a more interactive and engaging shopping experience